Analisis Bibliometrik Terhadap Pemetaan Riset Social Media Marketing - Herlina, Vivi (Jurnal Pekommas, 2022)
Social media marketing utilization is an evolving marketing tool rapidly. The objectives of this research are to map research trends of social media marketing on marketing performance and to know research productivity in terms of researchers, publishers, and citations. The bibliometric analysis method by using VOSviewer was used in this research. There were 493 articles from 2000 until 2021 of Google Scholar to be reviewed. The advantage of using Google Scholar as a data source is that it could generate more research than just a specific database. The results showed that most social media marketing research development took SMEs as the object. Whereas most articles were written by Eunju Ko. Network Visualizations showed there were seven clusters. Furthermore, Density Visualization indicates some related research to social media marketing, were medium, firm, social structure, advertising, digital marketing, and measurement. Meanwhile, the rare research consists of consumer behaviour, ROI, digital marketing, performance, the fast fashion industry, and luxury fashion brand. It has a meaning that there is an opportunity for future researchers in this field.